Evaluation of the Anticancer Properties of Geranyl Isovalerate, an Active Ingredient of Argyreia nervosa Extract in Colorectal Cancer Cells - Rasool, Fayyaz; Sharma, Deepu; Anand, P. Shanmukha; Magani, SKJ; Tantravahi, Srinivasan (Frontiers in Pharmacology, 2021)
Chemotherapy is a general treatment procedure for cancers. The diversity in cancer incidence and failure of therapy due to chemoresistance leads to increased cancer-related deaths. Therefore, new drugs with less secondary complications targeting diverse pathways are the need of the hour. Geranyl isovalerate (GIV), one of the active ingredients of ethyl acetate fraction of A.nervosa is routinely used as a food flavouring agent. In this study, we found that GIV also exhibits anticancer activity when tested against HCT 116 cell line. It has influenced the viability of the cells in a dose and time-dependent manner. We examined that GIV could induce oxidative stress and affect the mitochondrial membrane potential, thereby leading to apoptosis induction. Moreover, GIV could suppress the expression of antiapoptotic genes like BCl2 and PARP and induce the expression of proapoptotic genes like Caspase 3 and 9. This is the first study demonstrating the anticancer activity of GIV and providing evidence for its mechanism of action. In conclusion, our study proposes GIV as a potential lead or supplementary molecule to treat and prevent colorectal cancer.